Social Digital Objects for Grandparents - Pullin, Graham; Rogers, Jon; Banks, Richard; Regan, Tim; Napier, Ali; Duplock, Polly (Proceedings of Include 2011 conference on inclusive and people-centred design., 2011)
This paper describes a collaboration between the University of Dundee and Microsoft Research in which product design and interaction design students were asked to design digital products for older users. The project offered an introduction to inclusive design for the students. Rather than approach this in terms of designing for the whole population, they each designed with and for a particular grandparent. And rather than consider the accessibility of an existing product, they used this perspective to catalyse radical thoughts of future roles for digital technology. The various stages of the project are described, from initial user research through prototyping to final presentation at Microsoft's Design Expo in Redmond. Reflections are included from the audience at this event, the students, their tutors and our industrial partners. The paper ends with a short consideration of the role of digital technology in our everyday social interactions. At Microsoft this is part of Socio-Digital Systems research and at Dundee we have started to call this Social Digital.